Pastabos dėl baltų negimininių įvardžių „bikazualumo“ - Palmaitis, Letas (Baltistica, 1983)
Notes on the East-Baltic pronominal “bicasualism” The synonymous case-forms and the occasional quasi-bicasual paradigms of personal pronouns (e. g. Lith. sg. nom. aš – non-nom. mani, pl. nom. mes – non-nom. mumi) might have arisen in different ways by the neutralization, redistribution, generalization, etc. of the various case-forms, though the reason of all these processes was the original bicasualism of the pronominal system (e. g. pi. *mes – *nō(±-s)). The thing is that the formation of the nominatival four-case system took place in personal pronouns after it had taken place in nouns and on the basis of the latter. The same case inflection might have been added to different, not to the single (non-nominative) stem, though the number of such stems (e. g. *nōs, *nō) was fewer than of the current cases. Thus the nominative system paradigms of personal pronouns were “weak” from the very beginning and there is no sense to speak about the “Common-Baltic” paradigms of the type, e. g. nom. *mes, gen. *nōsōn, dat. *nōmōs, acc. *nōs, instr. *nōmīs, iness. *nōsu. Even in the East-Baltic (“Lithuanian-Latvian”) parent language there were no “classical” (i. e. “Suvalkized”) paradigms, the final formation of the declensional systems taking place after the split of East-Baltic. Thus Lith. instr. manimi, iness. manyje are late i-stem pattern innovations on the basis of the non-paradigmatical East-Baltic dat./loc. mani. Latvian manim (tevim, sevim) is an innovation spread from the dative where the final -m has occurred according to the pure Latvian datives singular in -m of nouns and adjectives. There are no traces of singular instrumentals in -m in Latvian nominal declension. The instrumental (and the form *manimi) has never existed in Prussian as well (III 10715 is “dat.” *mei with the postponed *-mi).